Нові методи управління на основі систем контролю фазових кутів напруг у головних вузлах енергосистеми - Lenchevsky Ye.A. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
Are carried out theoretical researches of development of the automated and automatic control systems on the basis of use of new monitoring systems of phase corners in the basic units of a power supply system. In work perspective directions on creation of new methods general system of managements, intended both for an oper¬ating mode of a power supply system, and in case of work antiemergency automatics are considered. The opportunity of sharing of angular characteristics of stations and lines is proved at management of a line mode, examples of their visual reflection are shown.